The Effect of hip motion exercises (stretching) on ​​the intensity of lower back pain in the elderly - Joko Sutejo; Reisy Tane (Jurnal Penelitian Keperawatan Medik, 2023)
Lower back pain in the elderly will cause changes in collagen, causing a decrease in flexibility in the elderly, causing an impact in the form of pain. One of the non-pharmacological actions that can be taken to treat low back pain (LBP) in the elderly is stretching, which is a stretching technique for soft tissue with certain techniques, to reduce muscle tension physiologically so that muscles relax and increase joint range of motion. The purpose of this study was to determine the effect of hip exercise (stretching) on the intensity of low back pain in the elderly. This type of research uses quantitative research with a pre-experimental research design using a one group pretest-posttest design. Data were analyzed using the Paired Sample T test. The. number of available samples was 30 samples taken by purposive sampling method. Data was collected by using observation sheets as many as 30 respondents. The results of the bivariate analysis obtained p-value 0,00 <0.05, which means that there is an effect of hip movement exercises (stretching) on the intensity of low back pain in the elderly. This research is expected to add insight into the effect of stretching exercises on the intensity of low back pain in the elderly and can be useful in health services, especially at the Puskesmas and become a source of information for implementing lower hip exercise interventions (stretching) on the intensity of low back pain in the elderly. as a non-pharmacological action